Lower GI Bleeding: An Update on Incidences and Causes - Adegboyega, Titilayo; Rivadeneira, David (Clinics in Colon and Rectal Surgery, 2020)
Bleeding from the lower gastrointestinal tract represents a significant source of morbidity and mortality. The colon represents the vast majority of the location of bleeding with only a much smaller incidence occurring in the small intestine. The major causes of lower gastrointestinal bleeding (LGIB) are from diverticulosis, vascular malformations, and cancer. We discuss the incidence and causes of LGIB.
Keywords: lower gastrointestinal bleeding; diverticulosis; vascular malformations; cancer; inflammatory bowel disease; hemorrhoids